Collaborative source–grid–load frequency regulation strategy for DC sending-end power grid considering electrolytic aluminum participation - Xing, Chao; Xi, Xinze; He, Xin; Deng, Can; Zhang, Mingqiang (Frontiers in Energy Research, 2024)
As renewable energy sources are increasingly integrated into the power system, traditional frequency regulation methods face challenges such as reducing system inertia and diminishing regulatory capacity. This paper presents a source-network-load collaborative control strategy for the participation of electrolytic aluminum in the frequency regulation of the DC sending-end power grid. Firstly, the frequency response characteristics of the UHVDC sending-end system are analyzed, and an electrolytic aluminum load model is established. Then, a hierarchical source-network-load control strategy is proposed. The upper-layer control strategy assigns frequency support tasks to synchronous generators, electrolytic aluminum stations and UHVDC systems based on the frequency dead zones. The lower-layer control aims to minimize the cost of controlling electrolytic aluminum loads by distributing power adjustment commands to each electrolytic aluminum series within the power station. The simulation results validate the effectiveness and economic benefits of the proposed strategy in reducing control costs and maintaining system stability.